2014
DOI: 10.2174/1573399810666140515113137
|View full text |Cite
|
Sign up to set email alerts
|

ALA, Fatty Fish or Marine n-3 Fatty Acids for Preventing DM?: A Systematic Review and Meta-Analysis

Abstract: Diabetes mellitus (T2DM) has become a global problem. Role of n-3 FA in its prevention is still not completely understood. We carried out this systematic review and meta-analysis to assess the relation of dietary intake of fish and n-3PUFA with risk of diabetes. We searched PUBMED, EMBASE and GOOGLE with cross references to identify relevant articles. Since no RCTs were available, we searched for prospective cohort studies. Sixteen studies with 6,79,763 participants which assessed the association of dietary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 0 publications
3
35
1
4
Order By: Relevance
“…These biological markers, however, reflect a shorter exposure duration relative to the one year assessment of traditional food intakes. Similar to our findings, in postmenopausal Chinese women BMD was 3.2-6.8% higher in the top quintile compared to lowest quintile of traditional sea fish intake [29] and higher frequency of intakes of fish in a meta-analysis associated with reduced risk of T2D [30]. Traditional food patterns including fish and seafood also associate with lower HbA1c [14].…”
Section: Discussionsupporting
confidence: 87%
“…These biological markers, however, reflect a shorter exposure duration relative to the one year assessment of traditional food intakes. Similar to our findings, in postmenopausal Chinese women BMD was 3.2-6.8% higher in the top quintile compared to lowest quintile of traditional sea fish intake [29] and higher frequency of intakes of fish in a meta-analysis associated with reduced risk of T2D [30]. Traditional food patterns including fish and seafood also associate with lower HbA1c [14].…”
Section: Discussionsupporting
confidence: 87%
“…Poor insulin sensitivity is associated with T2DM and metabolic syndrome [10, 11]. The results of randomized control trials (RCTs) investigating the association between n-3 PUFA and insulin sensitivity were inconsistent [1215].…”
Section: Introductionmentioning
confidence: 99%
“…Several prospective cohort studies reported protective effects of fish consumption and n-3 FAs intake on the risk of T2D (Patel et al 2009;Nanri et al 2011;Villegas et al 2011), whereas some studies suggest positive (Kaushik et al 2009;Djoussé et al 2011) or no associations (van Woudenbergh et al 2009). Meta-analyses reported geographical differences in the associations between fish consumption, n-3 FAs, and the development of T2D; a protective association was observed in the populations of Asian countries, and a positive association was observed in the American population (Muley et al 2014). …”
Section: Introductionmentioning
confidence: 99%